1999
DOI: 10.1136/bmj.318.7179.295
|View full text |Cite
|
Sign up to set email alerts
|

Current status of long term ventilation of children in the United Kingdom: questionnaire survey

Abstract: Objectives To identify the number and current location of children, aged 0 to 16 years, requiring long term ventilation in the United Kingdom, and to establish their underlying diagnoses and ventilatory needs. Design Postal questionnaires sent to consultant respiratory paediatricians and all lead clinicians of intensive care and special care baby units in the United Kingdom. Subjects All children in the United Kingdom who, when medically stable, continue to need a mechanical aid for breathing. Results 141 chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
108
1
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(114 citation statements)
references
References 13 publications
3
108
1
2
Order By: Relevance
“…A recent review of UK children requiring long-term respiratory support at home showed that 56% of the surveyed population used mask ventilation [9]. The range of conditions that has benefited from this form of noninvasive support continues to grow throughout the pediatric age group [20,21,22,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review of UK children requiring long-term respiratory support at home showed that 56% of the surveyed population used mask ventilation [9]. The range of conditions that has benefited from this form of noninvasive support continues to grow throughout the pediatric age group [20,21,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Advantages of home mechanical ventilation (HMV) include decreased hospital-acquired infections, improved nutritional status, physical and physiological function and quality of life, resumption of more normal interactions and routines of daily life and lower health care costs [3,4,5,6]. The cumulative number of children who were started on HMV has increased tremendously in Europe and North America but little is known about HMV use and outcomes in children in developing countries [7,8,9,10,11]. Although Istanbul is quite a modern city, there are obstacles in starting HMV in children such as a lack of insurance support for home nursing and home visits of respiratory therapists.…”
Section: Introductionmentioning
confidence: 99%
“…Comparando-se a casuística do programa por nós avaliado com estudo realizado na Inglaterra na última década, que analisa a evolução das crianças em assistência ventilatória domiciliar, observam-se muitas semelhanças 8 . No estudo inglês, assim como no programa de assistência ventilatória domiciliar do Dr. von Haunersches Kinderklinik, a maioria das crianças com insuficiência respiratória crônica apresentava doenças neuromusculares (55,9%), seguida pela síndrome de hipoventilação central congênita (14,0%).…”
Section: Discussionunclassified
“…35,36 Although no other studies have addressed the rehospitalization rates for children with tracheostomy, before and after decannulation, several have found that children who are ventilator dependent at home have a higher risk of rehospitalization than other children. 11,12,[36][37][38][39] The decrease in readmission rate after decannulation may be secondary to removal of the tracheostomy, improvement in BPD, or both.…”
Section: Figurementioning
confidence: 99%